Molecular characterization and T and B cell epitopes prediction of Mycoplasma synoviae 53 strain VlhA hemagglutinin - Ilana Lopes Camargo; Cristina Toscano Fonseca; Santuza Ribeiro Teixeira; Vasco Azevedo; Anderson Myioshi; Sergio Costa Oliveira (Genetics and Molecular Biology, 2007)
Mycoplasma sinoviae is a major pathogen of poultry causing synovitis and respiratory infection. M. synoviae hemagglutinin (VlhA) is a lipoprotein encoded by related multigene families that appear to have arisen by horizontal gene transfer. It is an abundant immunodominant surface protein involved in host-parasite interaction mediating binding to host erythrocytes. Herein, we have performed in silico analysis of the vlhA gene product from the Mycoplasma synoviae 53 strain and compared it to the VlhA protein of M. synoviae WUV1853 strain. The VlhA of the M. synoviae 53 strain possesses 569 amino acids and showed 85% identity with the VlhA protein of the M. synoviae WUV1853 strain. Further, a signal peptide was identified from amino acid M1 to D28 and a cleavage site between D28 and Q29, both located in the N-terminal domain of the molecule. Additionally, an insertion of PAPT amino acids was observed between T30-P35 and a deletion of the amino acids GTPGNP within the PRR region of the VlhA from the M. synoviae 53 strain, which may be related to its reduced virulence. Finally, we have identified 17 B cell epitopes and 22 T cells epitopes within the VlhA from the M. synoviae 53 strain. The B cell epitope S263-D277 and the T cell epitopes N45-N54 and G58-N67 showed 100% and 87-100% identity, respectively, with regions of VlhA protein of tested Mycoplasma synoviae and Mycoplasma galisepticum strains. Thus, these peptides represent new candidate molecules for the development of efficient diagnostic assays and new subunit vaccines.